1994
DOI: 10.1042/bj3040391
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the rat lactate dehydrogenase A subunit gene promoter/regulatory region

Abstract: The rat lactate dehydrogenase (LDH) A subunit gene promoter contains a putative AP-1 binding site at -295/-289 bp, two consensus Sp1 binding sites at -141/-136 bp and -103/-98 bp, and a single copy of a consensus cyclic AMP-responsive element (CRE) at -48 to -41 bp upstream of the transcription initiation site. Additionally, an as yet unidentified silencer element is located within the -1173/-830 bp 5'-flanking region. Transient transfection analyses of a -1173/+25 bp LDH A-chLoramphenicol acetyltransferase fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 43 publications
2
31
0
Order By: Relevance
“…Baf-3 cells were transduced with either full-length Sp1 or Sp1DZn and examined thirty hours later. Transduced full-length Sp1 was transcriptionally active as purified Sp1-infected cells showed increased mRNA levels coding for lactate deshydrogenase (LDH) A (Figure 5a), a gene which basal expression level is regulated by Sp1 (Short et al, 1994). As expected, transduced Sp1DZn did not induce LDH-A transcription although the protein expression Apoptosis induction by Sp1 E Deniaud et al levels of Sp1DZn were higher than Sp1 expression levels (Figure 5b).…”
Section: Apoptosis Induction By Sp1mentioning
confidence: 64%
“…Baf-3 cells were transduced with either full-length Sp1 or Sp1DZn and examined thirty hours later. Transduced full-length Sp1 was transcriptionally active as purified Sp1-infected cells showed increased mRNA levels coding for lactate deshydrogenase (LDH) A (Figure 5a), a gene which basal expression level is regulated by Sp1 (Short et al, 1994). As expected, transduced Sp1DZn did not induce LDH-A transcription although the protein expression Apoptosis induction by Sp1 E Deniaud et al levels of Sp1DZn were higher than Sp1 expression levels (Figure 5b).…”
Section: Apoptosis Induction By Sp1mentioning
confidence: 64%
“…However, it has been shown that (a) bFGF increases transferrin and LDH A mRNA levels in rat Sertoli cells (Han et al 1993, (b) transferrin and LDH A gene promoters contain CRE-like and CRE sequences respectively (Short et al 1994, Chaudhary & Skinner 1999 and (c) MAPK relays the signal downstream by activating various proteins in the cell, including gene regulatory proteins like Elk-1, c-myc and CREB (Alvarez et al 1991, Marais et al 1993, Ginty et al 1994, Xing et al 1996. Taking into account this information, it is tempting to speculate that increased levels of phosphorylated CREB in response to bFGF might be involved in the regulation of transferrin and LDH A gene transcription.…”
Section: Discussionmentioning
confidence: 99%
“…The rat LDH-A promoter contains two consensus Myc͞Max binding sites or E-boxes, CACGTG (located at Ϫ78 through Ϫ83 and Ϫ175 through Ϫ180 from the transcriptional start site), that are conserved in mouse and man, suggesting that c-Myc may regulate the transcription of LDH-A through these sites (8,50). Transient transfection experiments with a c-Myc expression vector demonstrated an E-box-dependent transactivation of the LDH-A promoter-luciferase reporter gene (Fig.…”
Section: Ldh-a Is a Target Of C-mycmentioning
confidence: 99%
“…The LDH-A gene is an epidermal growth factor, cAMP and phorbol ester-inducible delayed early serum response gene whose role in neoplasia remains unestablished despite its widespread use as a prognostic tumor marker (5)(6)(7)(8). LDH is a tetrameric enzyme with five isoforms composed of combinations of two subunits, LDH-A and LDH-B.…”
mentioning
confidence: 99%